Rentabilidad de la Empresa Bananera Hacienda Contreras S.A. - Rendón Vizcaíno, Diana Leonor (2017)
Banana companies represent the greatest source of work in the province of rivers. At present, banana farms face a series of problems that have been affecting their economy, the effects of pests on their production, climate factors, informality in the internal market of bananas causes that official prices are hardly respected. This research was carried out at the Contreras farm, a company located in the canton Pueblo viejo of the province of Los Ríos which has 30 hectares, and its main activity is banana production. Such production is sold internally since the company is not an exporter, so it needs intermediaries for the sale of its product. For the year 2016 the hacienda has experienced a decrease in its usefulness compared to the year 2015, reasons for which the present case study was developed which has been denominated: Profitability of the banana company hacienda Contreras S.A. The profitability that an entrepreneur hopes to obtain is the motivation in itself, by which the production activities are exercised. Knowing the margins of profitability is indispensable for decision making.